Thick concepts and moral revisionism in Plato’s Gorgias: arguing about something there can be no argument about - Brüllmann, Philipp (Phronesis, 2019)
Abstract David Furley has suggested that we think of Callicles’ immoralism as attacking a thick concept. I take up this suggestion and apply it to the argument of Plato’s Gorgias more generally. I show that the discussion between Socrates, Gorgias and Polus, which prepares the ground for Callicles, is precisely addressing the thickness of the concept of justice: it reveals that this concept is both descriptive and evaluative and that formulating a revisionist position about justice is therefore extremely difficult. Callicles’ strategy is best read as a response to this difficulty, which sets the stage for Socrates’ revisionist account of justice.
Gesehen am 11.02.2026